Problems in Fish-to-Tetrapod Transition: Genetic Expeditions Into Old Specimens - Wood, Thomas W. P.; Nakamura, Tetsuya (Frontiers in Cell and Developmental Biology, 2018)
The fish-to-tetrapod transition is one of the fundamental problems in evolutionary biology. A significant amount of paleontological data has revealed the morphological trajectories of skeletons, such as those of the skull, vertebrae, and appendages in vertebrate history. Shifts in bone differentiation, from dermal to endochondral bones, are key to explaining skeletal transformations during the transition from water to land. However, the genetic underpinnings underlying the evolution of dermal and endochondral bones are largely missing. Recent genetic approaches utilizing model organisms – zebrafish, frogs, chickens, and mice – reveal the molecular mechanisms underlying vertebrate skeletal development, and provide new insights for how the skeletal system has evolved. Currently, our experimental horizons to test evolutionary hypotheses are being expanded to non-model organisms with state-of-the-art techniques in molecular biology and imaging. An integration of functional genomics, developmental genetics, and high-resolution CT scanning into evolutionary inquiries allows us to reevaluate our understanding of old specimens. Here, we summarize the current perspectives in genetic programs underlying the development and evolution of the dermal skull roof, shoulder girdle, and appendages. The ratio shifts of dermal and endochondral bones, and its underlying mechanisms, during the fish-to-tetrapod transition are particularly emphasized. Recent studies have suggested the novel cell origins of dermal bones, and also the interchangeability between dermal and endochondral bones, obscuring the ontogenetic distinction of these two types of bones. Assimilation of ontogenetic knowledge of dermal and endochondral bones from different structures demands revisions of the prevalent consensus in the evolutionary mechanisms of vertebrate skeletal shifts.